1991
DOI: 10.1007/978-94-011-3792-8_21
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of substrate-associated juveniles of the genus Sebastes

Abstract: SynopsisThis paper reviews current knowledge of substrate-associated juvenile Sebastes. In general, juvenile rockfish recruit to shallower depths than those occupied by conspecific adults. Habitat use by newly recruited rockfish differs markedly among species. While a few species recruit to shallow-dwelling macrophytes, such as Zostera, many others recruit to larger brown algae, such as Nereocystis and Macrocystis. A few deeper dwelling species recruit to low relief or soft substrata. However, little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 45 publications
4
71
0
Order By: Relevance
“…While several authors (Bayer 1981;Love et al 1991;Shaffer et al 1995;Buckley 1997) have observed juvenile rockfish strongly associated with various types of habitat (eelgrass, kelp, and drift vegetation), this work shows a general gradient wherein a greater abundance of age-0 black rockfish occurs within complex anthropogenic habitat (docks, seawalls, and jetties), leading us to question how continued estuarine development might affect rockfish populations. Within the estuary, minnow traps consistently captured the largest numbers of rockfish within areas of high habitat complexity (docks and pilings).…”
Section: Rockfish Essential Habitat Identificationmentioning
confidence: 73%
“…While several authors (Bayer 1981;Love et al 1991;Shaffer et al 1995;Buckley 1997) have observed juvenile rockfish strongly associated with various types of habitat (eelgrass, kelp, and drift vegetation), this work shows a general gradient wherein a greater abundance of age-0 black rockfish occurs within complex anthropogenic habitat (docks, seawalls, and jetties), leading us to question how continued estuarine development might affect rockfish populations. Within the estuary, minnow traps consistently captured the largest numbers of rockfish within areas of high habitat complexity (docks and pilings).…”
Section: Rockfish Essential Habitat Identificationmentioning
confidence: 73%
“…Species that undergo parturition primarily during the spring and summer, including some nearshoredemersal species and species of the subgenus Sebastomus that occupy deeper benthic habitats on the inner shelf (Chen 1971, Love et al 1991, Lenarz et al 1995, are most likely to comprise the assemblage of larval rockfishes in our samples. Concentrations of larval rockfishes occurred at fronts well offshore of the distribution of adults of these species (which is restricted by the narrow continental shelf off the Big Sur coast) and thus apparently reflect the effects of transport following parturition.…”
Section: Origins Of Patches Of Larval Rockfishes At Frontsmentioning
confidence: 96%
“…exhibit early life histories that are in many ways functionally intermediate to life histories typified by intertidal invertebrates and coastal pelagic fishes: like pelagic fishes, rockfishes undergo substantial growth and development in the pelagic habitat, developing from small (3 to 7 mm) larvae into pelagic juveniles 20 to 70 mm in length prior to settlement to benthic habitats, yet, like intertidal invertebrates, many species of rockfishes must return to nearshore habitats to complete the life cycle (Love et al 1991, Moser & Boehlert 1991. Empirical relationships between rockfish recruitment and upwelling intensity (Norton 1987, Ainley et al 1993, Ralston & Howard 1995 exhibit characteristics of both dome-shaped relations indicative of optimal conditions for larval feeding (Cury & Roy 1989), and inverse relations indicative of the effects of transport on larval supply to adult habitats (Farrell et al 1991, Wing et al 1995a.…”
Section: Introductionmentioning
confidence: 99%
“…The copper rockfish was the only other species found to move between monitored platforms (Table 3), providing further evidence for successful emigration. Conversely, vermilion rockfish are thought to be highly site specific (Hartmann 1987;Lea et al 1999), but like many species of rockfishes they are known to exhibit ontogenetic movements to deeper water as they grow and mature (Love et al 1991;Love 1996;Lea et al 1999). Some of the variation in degree of site fidelity GROUNDFISH SITE FIDELITY AND MOVEMENT PATTERNS among vermilion rockfish was attributed to the depth of platforms where individuals were tagged.…”
Section: Groundfish Site Fidelity and Movement Patternsmentioning
confidence: 99%